Coexistence of imipenemase (IMP) and verona integron-encoded metallo-beta-lactamase (VIM) in gram-negative bacterial clinical isolates from Ouagadougou, Burkina Faso - Amana Metuor-Dabiré; Damis Y. P. Bouniounou; Nicolas Ouédraogo; Rahimatou Y. Tiemtoré; Serge Sougué; Rose P. Bonkoungou; Jacques Simporé (Microbiology Independent Research Journal)
INTRODUCTION: Escherichia coli , Pseudomonas aeruginosa , and Klebsiella oxytoca are among the most frequently isolated pathogens implicated in human disease in Burkina Faso. In addition, the emergence of carbapenem-resistant E. coli , P. aeruginosa , and K. oxytoca due to the production of IMP and VIM enzymes and the spread of these bacteria is a real concern for health facilities. However, the coexistence of the resistance genes encoding these enzymes in clinical bacterial isolates from Burkina Faso has not been previously reported. OBJECTIVE: To prove the coexistence of VIM and IMP in E. coli , P. aeruginosa and K. oxytoca clinical isolates from two medical centers in Ouagadougou, Burkina Faso, by means of conventional PCR. METHODS: Antibiotic susceptibility testing of 158 gram-negative bacilli isolates was performed against carbapenems and aztreonam using the disk diffusion method. The resistant isolates were screened using conventional polymerase chain reaction for the bla VIM and bla IMP genes. RESULTS: E. coli (45.1%, 41 isolates) was the most common among the resistant species, with a higher level of resistance to ertapenem (20.9%, 19 isolates) from all the carbapenems. P. aeruginosa (9.9%, 9 isolates) and K. oxytoca (1.1%, one isolate) were less common resistant species. The genes bla VIM and bla IMP were detected simultaneously in only 5.5% (5 isolates) of the resistant bacterial strains, including three strains of E. coli , one strain of P. aeruginosa , and one strain of K. oxytoca . CONCLUSION: This study established the coexistence of bla VIM and bla IMP genes in E. coli , P. aeruginosa , and K. oxytoca strains isolated from patients at the Centre Hospitalier Universitaire de Tengandogo and the Hôpital Saint Camille de Ouagadougou in Burkina Faso. These bacterial isolates were resistant to carbapenems due to the production of VIM and IMP enzymes.